Jewish Popular Music in Galicia: Karol Rathaus’ Recollections of Chune Wolfsthal - Guzy-Pasiak Jolanta (Musicology Today)
Eminent Polish composer Karol Rathaus (1895–1954) left behind an essay dedicated to his uncle Chune Wolfsthal (1851–1924). In this text, Rathaus recalls his childhood and adolescent years in (Austria-Hungary’s crown land of ) Galicia. His memories of Wolfsthal, a famous klezmer and operetta composer active in the late nineteenth and early twentieth centuries, provide an opportunity to recollect the now non-existent world of Jewish amateur musicians working in Tarnopol and Lwów before World War II. Those musicians performed in synagogues, at family events and social functions, in cafés and tea gardens. Some of them, including Chune, became involved in the activity of the then emerging Jewish theatre, which was a part-vulgar, part-artistic phenomenon.